-FOREWORD- Tectonic and magmatic evolution of Mexico during the Cenozoic - Gerardo de Jesús Aguirre-Díaz (Revista Mexicana de Ciencias Geológicas)
On May, 1997, the IV Symposium on the Cenozoic Tectonics and Volcanism of Mexico was organized, within the II Convention on the Geologic Evolution of Mexico, that took place in Pachuca, Hidalgo, Mexico. Several papers were presented in this symposium, that included the state of the art in these topics. Due to the high quality of the new data shown during the symposium, it was decided to gather these works in a special volume and publish them in order that the scientific community and public in general could have access to them in a journal with high publishing quality and good diffusion in Mexico and other countries... In order to continue, download the full PDF.